The Application of Employee Job Training at the Level of Production Quality of the Café RD Business Analyzes the Results of the Evaluation of the Productivity of Employee Performance From Year to Year in the Café RD MSME Business Lubug Begalung - Marta Widian Sari; Mahmuda Sitorus; Hammar Faris; Gilbert Yonanda; Ahmad Septu Naufal; Naufal Abbian Akbar (LPPM UIKA Bogor, 2023)
This Community Service Program (PKM) aims to identify and increase the owner's understanding and knowledge of how to train employees to support a competitive advantage in the competition in order to increase business income and can recommend the right mix of strategies or compositions. In this Community Service, there are 4 stages for the method that has been passed which consists of preparation, screening, implementation of activities and evaluation. The results of this PKM show that socialization to workers can increase competitiveness in the tempe and toge business (Blessing), and motivate employees to increase production quality. It is also hoped that this PKM activity will also have an impact on increasing the insight and understanding of business owners on how to make quality performance.